Evaluation of the side effects of poly(epsilon-caprolactone) nanocapsules containing atrazine toward maize plants - Oliveira, Halley C.; Stolf-Moreira, Renata; Martinez, Cláudia B. R.; Sousa, Gustavo F. M.; Grillo, Renato; de Jesus, Marcelo B.; Fraceto, Leonardo F. (Frontiers in Chemistry, 2015)
Poly(epsilon-caprolactone) (PCL) nanocapsules have been used as a carrier system for the herbicide atrazine, which is commonly applied to maize. We demonstrated previously that these atrazine containing polymeric nanocapsules were ten-fold more effective in the control of mustard plants (a target species), as compared to a commercial atrazine formulation. Since atrazine can have adverse effects on non-target crops, here we analyzed the effect of encapsulated atrazine on growth, physiological and oxidative stress parameters of soil-grown maize plants (Zea mays L.). One day after the post-emergence treatment with PCL nanocapsules containing atrazine (1 mg mL-1), maize plants presented 15 and 21 % decreases in maximum quantum yield of photosystem II and in net CO2 assimilation rate, respectively, as compared to water-sprayed plants. The same treatment led to a 1.8-fold increase in leaf lipid peroxidation in comparison with control plants. However, all of these parameters were unaffected four and eight days after the application of encapsulated atrazine. These results suggested that the negative effects of atrazine were transient, probably due to the ability of maize plants to detoxify the herbicide. When encapsulated atrazine was applied at a ten-fold lower concentration (0.1 mg mL-1), a dosage that is still effective for weed control, no effects were detected even shortly after application. Regardless of the herbicide concentration, neither pre- nor post-emergence treatment with the PCL nanocapsules carrying atrazine resulted in the development of any macroscopic symptoms in maize leaves, and there were no impacts on shoot growth. Additionally, no effects were observed when plants were sprayed with PCL nanocapsules without atrazine. Overall, these results suggested that the use of PCL nanocapsules containing atrazine did not lead to persistent side effects in maize plants, and that the technique could offer a safe tool for weed control without affecting crop growth.